Oliver Scharbrodt y Yafa Shanneik, eds. 2020. Shi‘a Minorities in the Contemporary World. Migration, Transnationalism and Multilocality. Edimburgo: Edinburgh University Press. 344 pp. ISBN 9781474430371 - Taussig, Sylvie (Estudios de Asia y África, 2022)
Oliver Scharbrodt y Yafa Shanneik, eds. 2020. Shi‘a Minorities in the Contemporary World. Migration, Transnationalism and Multilocality. Edimburgo: Edinburgh University Press. 344 pp. ISBN 9781474430371